Apolipoprotein Proteomic Profiling for the Prediction of Cardiovascular Death in Patients with Heart Failure. Issue 6 (28th September 2020) - Lemesle, Gilles; Chouraki, Vincent; de Groote, Pascal; Turkieh, Annie; Beseme, Olivia; Drobecq, Hervé; Amouyel, Philippe; Lamblin, Nicolas; Bauters, Christophe; Pinet, Florence
Abstract : Purpose: Risk stratification in chronic systolic heart failure (HF) is critical to identify the patients who may benefit from advanced therapies. It is aimed at identifying new biomarkers to improve prognosis evaluation and help to better understand HF physiopathology. Experimental design: Prognostic evaluation is performed in 198 patients with chronic systolic HF: 99 patients who died from cardiovascular cause within three years are individually matched for age, sex, and HF etiology (ischemic vs not) with 99 patients who are alive after three years of HF evaluation. A proteomic profiling of 15 apolipoproteins (Apo) is performed: Apo‐A1, ‐A2, ‐A4, ‐B100, ‐C1, ‐C2, ‐C3, ‐C4, ‐D, ‐E, ‐F, ‐H, ‐J, ‐L1, and ‐M using LC‐MRM‐MS. Results: In univariate analysis, the levels of Apo‐B100 and ‐L1 are significantly lower and the levels of Apo‐C1, ‐J, and ‐M are significantly higher in patients who died from cardiovascular cause as compared with patients alive. In the final statistical model, Apo‐C1, Apo‐J, and Apo‐M improve individually the prediction of cardiovascular death. Ingenuity pathway analysis indicates these three Apo in a network associated with lipid metabolism, atherosclerosis signaling, and retinoid X receptor activation. Conclusions: Proteomic profiling of apolipoproteins using LC‐MRM‐MS might be useful in clinical practice for risk stratification of HF patients.